Clinical Medical Record Audit Description For Quality Control And Cost Control In Healthcare Services At Dharma Yadnya General Hospital Denpasar: A Qualitative Study - Nichia Trinity Luisa Walangitan; Anak Agung Gde Oka Widana; I Gusti Agung Ngurah Putra Pradnyantara (International Journal of Health Engineering and Technology, 2026)
Clinical audit of medical records is an important effort to improve the quality of healthcare services and control costs in hospitals. However, inconsistent implementation and incomplete medical record documentation can affect its effectiveness. This study aimed to examine the implementation of clinical audits of medical records in supporting quality control and cost control at RSU Dharma Yadnya Denpasar. This study used a descriptive qualitative method, with data collection techniques including interviews and observations, and the data were analyzed using the Colaizzi 7-step method. The results showed that the implementation of clinical audits of medical records has followed a process in accordance with the Standard Operating Procedures (SOP), including sample selection, assessment, analysis, and the provision of recommendations. However, in practice, several discrepancies were found, such as audit implementation that was not consistently carried out according to schedule and incomplete medical record documentation. These conditions have resulted in the audit function not being optimal in supporting quality control and have caused obstacles in the claim process, thereby affecting cost control. Therefore, clinical audits of medical records play an important role in supporting quality and cost control; however, their implementation needs to be improved through consistent scheduling and increased compliance of healthcare personnel in completing medical records.